ANALISIS PENGARUH PERILAKU KEPEMIMPINAN PENGUSAHA KECIL TERHADAP BUDAYA KERJA (Studi Kasus pada Pengusaha Kecil Bidang Konstruksi di Kota Palu) - Mahardiana, Lina (Buletin Studi Ekonomi, 2013)
Small business engaged in construction, to be able to survive a failure  depend on the orientation of its leadership  runs the business which is it will affect work culture. Effective leaders simultaneous task-oriented and relationship-oriented. Tthe highest attention devoted to the production and human. The results showed that the behavior of task-oriented leadership and relationships-oriented affect work culture proposed  by Hofstede. Leadership behaviors significantly influence the work culture at a very large power distance, uncertainty avoidance is huge, including the category of high individualistic and masculinity are high as well.
Keywords: small business, leadership behavior, work culture